(untitled) - Battley, Susan (San Francisco, CA, 2006)
Coached to Lead is the first consumer’s guide to executive coaching. Drawing on her twenty years of experience and direct research with an elite international clientele, renowned CEO coach Susan Battley offers step-by-step advice for achieving the same extraordinary results that top leaders get from executive coaching. Filled with insider tips, engaging real-life cases, and handy checklists and sample documents, Coached to Lead will help anyone who considers working with a professional coach to make smart decisions that maximize valuable resources. Battley reveals all the insider secrets about coaching—how to determine your coaching readiness, how to choose the right coach, and how to use a winning five-step coaching model. She covers all the issues commonly raised as well as not-so-obvious situations and troubleshooting.
Keywords: Executive coaching,Executives,Executives,Executive ability,Leadership; Training of,Attitudes,Study and teaching